(untitled) (Global Journal of Management and Business Research, 2019)
The work environment which encompasses several factors impacts on the way the employees perform their work. Comfortable and all inclusive working environment will boost the employees’ performance hence boosting the organizational performance. The objective of the study was to investigate the effect of working environment on employee performance in the Etho-Telecom in Ambo branch. The target population was all the employees at Etho-Telecom. The total number was 102 and the study was included all the employees by using census study. Descriptive research design was adopted for the study. The study used primary data which was collected by used of semi structured and structured questionnaire. The findings of the study concluded that work environmental factors that influenced employee performance were organizational work environment factors, workplace relationship and organization cultural factors The study found out that employees’ performance was positively influenced by several work environment factors.